E-Commerce Under Electronic Transactions Act; Enhancing The Sri Lankan Legal Framework With Singapore’s Experience - Thrimasha, G. (The Department of Law, Faculty of Arts, University of Jaffna / Surana and Surana International Attorneys India, 2025)
The advent of the Internet has transformed the traditional business epoch, propelling what is popularly recognized as ‘e-commerce’. The advancement of information technology and telecommunication further accelerated this shift towards e-commerce where people abundantly experience formation of legal contracts in cyber-space. However, this has created new challenges that were less prominent in the conventional business landscape. Sri Lankan law relating to e-transactions is found primarily in the Electronic Transactions Act No. 19 of 2006 as amended by the Act No. 25 of 2017, based on the UNCITRAL Model Law and UN Convention on use of e-Communication in International Contracts. This paper seeks to examine Sri Lankan law on e-commerce contrasting it with the strengths in Singapore’s legislative framework which is known for its robust digital laws. The analysis is structured around the key statutory provisions of both jurisdictions that facilitate authenticity and legal recognition of e-records and e-signatures. Whilst numerous studies have been done on Sri Lankan laws that facilitate e-commerce in general, there is a dearth of research to understand whether there is adequate protection under the existing Sri Lankan legal framework that guarantees the rights and interests of parties relying on e-records and e-signatures when trading electronically. This paper employs a qualitative analysis of the related legislation and secondary sources and demonstrates how the differences in legislative approach in the selected jurisdictions on reforms strengthening e-commerce have led to noticeably different outcomes. The paper finds that Singapore has cautiously identified its priorities in e-commerce and has guaranteed adequate protection to all stakeholders including the global business community in their legal system. The paper concludes that despite the progressive strides taken, Sri Lanka must reinforce its legal framework to align with global best practices in order to instil user confidence in e-commerce.
Keywords: e-commerce; e-signatures; Sri Lanka; Singapore; Global best practices